2014
DOI: 10.1002/asia.201301500
|View full text |Cite
|
Sign up to set email alerts
|

Transition‐Metal‐Catalyzed CS Bond Coupling Reaction

Abstract: Sulfur-containing molecules such as thioethers are commonly found in chemical biology, organic synthesis, and materials chemistry. While many reliable methods have been developed for preparing these compounds, harsh reaction conditions are usually required in the traditional methods. The transition metals have been applied in this field, and the palladium-catalyzed coupling of thiols with aryl halides and pseudo halides is one of the most important methods in the synthesis of thioethers. Other metals have also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
129
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 437 publications
(133 citation statements)
references
References 126 publications
2
129
0
2
Order By: Relevance
“…1c). 28 We first investigated several transition metal precatalysts 13,29,30 in combination with iodobenzene for modifying MGS-His 6 . Major emphasis was placed on palladium 31 as a suitable metal mediator, as previous studies have shown its versatility in aqueous Suzuki- 13,32 and Sonogashira-coupling reactions.…”
Section: Scheme 1 Established Strategies Compared To Metalsite Guidementioning
confidence: 99%
“…1c). 28 We first investigated several transition metal precatalysts 13,29,30 in combination with iodobenzene for modifying MGS-His 6 . Major emphasis was placed on palladium 31 as a suitable metal mediator, as previous studies have shown its versatility in aqueous Suzuki- 13,32 and Sonogashira-coupling reactions.…”
Section: Scheme 1 Established Strategies Compared To Metalsite Guidementioning
confidence: 99%
“…But this approach is not suitable for molecules containing sensitive functional groups. [3] The development in recent years of transition-metal catalysts, [4] including copper [5] or palladium [6] catalysts, for C-S bond formation through the reaction of aryl halides and thiols means that reactions can now proceed under mild reaction conditions. But although the fact that harsh reaction conditions can now be avoided represents an important achievement, these methods still suffer from a disadvantage.…”
Section: Introductionmentioning
confidence: 99%
“…are some notable sulfur containing drug molecules. [8] Similarly, Ni, Co, Pd, or Cu metal catalyzed coupling reactions of aryl halides or template assisted synthesis are described in Figure 1a and Figure 1b, respectively. [4] For many years, synthesis of CÀS bonds [5] were usually based on the transition metal catalyzed cross couplings [6] of aryl halides with thiophenols.…”
Section: Introductionmentioning
confidence: 99%